Research assessment exercises in United Kingdom universities - learning to innovate. (1st January 2000) - Ball, Derrick F.; Butler, Jeff
Research assessment exercises covering universities in the United Kingdom were established to produce quality ratings as a basis for allocating much of the research funding from central government. They represent some of the largest research management exercises ever undertaken. This paper describes the way in which quality was assessed and funds were allocated as a result of the 1992 and 1996 exercises and looks at how the exercises are continuing to evolve. University research management systems can be compared with company R&D management systems. This should interest research administrators and project teams in universities as well as managers in industry; each can learn from understanding more clearly the management styles, cultures and experiences of the other.